2017
DOI: 10.1002/macp.201600443
|View full text |Cite
|
Sign up to set email alerts
|

The First Vanadium-Oxide-Based UHMWPE Catalyst Supported on Chemically Modified Silica Gel

Abstract: Novel vanadium‐oxide‐based catalysts supported on alumina, zirconia, or titania‐modified silica, which are able to synthesize ultrahigh molecular weight polyethylene (UHMWPE), are successfully developed. Compared with the unmodified silica supported catalyst, the activities of the modified catalysts are substantially enhanced. By changing the polymerization temperature (Tp) from 90 to 60 °C, the molecular weight of the produced UHMWPE can be easily regulated from 2 × 106 to more than 6 × 106 g mol−1. It is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…The effects of sulfation on VO x /SiO 2 –MO y (M = Al, Zr, or Ti) catalysts for the synthesis of UHMWPE are investigated systematically. Under the same polymerization conditions, the sulfated catalysts show activity about twice as high as that of the ones modified by metal oxide only, and even four times higher than that of the SiO 2 supported one . The characterization results of NH 3 –TPD indicate that the acidity of the catalysts is improved largely after sulfation, while the results of pyridine‐adsorption‐FTIR imply that a large amount of Lewis acid sites and a small amount of Brønsted acid sites are available on the surface of the catalysts.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The effects of sulfation on VO x /SiO 2 –MO y (M = Al, Zr, or Ti) catalysts for the synthesis of UHMWPE are investigated systematically. Under the same polymerization conditions, the sulfated catalysts show activity about twice as high as that of the ones modified by metal oxide only, and even four times higher than that of the SiO 2 supported one . The characterization results of NH 3 –TPD indicate that the acidity of the catalysts is improved largely after sulfation, while the results of pyridine‐adsorption‐FTIR imply that a large amount of Lewis acid sites and a small amount of Brønsted acid sites are available on the surface of the catalysts.…”
Section: Resultsmentioning
confidence: 87%
“…It is obvious that all the catalysts show an optimum Al/V at which the maximum activity is reached, as the cocatalysts act as alkylation reagent for active centers and scavenger for reaction system, but overdose of cocatalyst would result in deactivation through overreduction of the active centers . The optimum Al/V for VO x /SiO 2 –Al 2 O 3 –SO 4 2− , VO x /SiO 2 –ZrO 2 –SO 4 2− and VO x /SiO 2 –TiO 2 –SO 4 2− are 60, 60, and 70, respectively, and the maximum activity is similar for each catalyst at 2200 kg PE mol −1 V, which is equal to or lower than the activity of some supported V‐based Ziegler‐Natta catalysts, but is definitely higher than that of VO x /SiO 2 –MO y (M = Al, Zr, or Ti) at 1200 kg PE mol −1 V . This confirms that the sulfation indeed helps to improve the activity of the vanadium‐oxide‐based catalysts for ethylene polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Christman has reported Cl 3 CCOOEt or chlorinated hydrocarbons to be an effective reagents for maintaining the higher (active) oxidation state of vanadium systems, thus improving the catalytic activity of the vanadium‐based catalysts . Jin et al studied the effect of cocatalyst types on the activity of the sulfate‐modified VO x /SiO 2 –TiO 2 catalyst, also observing that the cocatalyst dependence on catalytic activity had the priority of DEAC > TIBA > TEA . It is suggested that the chloride of Al‐alkyl with weak reducibility and strong oxidizability retard the over‐reduction of vanadium active centers and the V–Cl–Al bridging bond also accounts much for the higher activity than TEA and TIBA .…”
Section: Resultsmentioning
confidence: 99%